Perbedaan Kompetensi Profesional Guru Matematika SD Melalui KKG Yang Dibina Meqip Dengan Yang Tidak Dibina Meqip Di Kabupaten Barru - Hj Karliati (Universitas Negeri Makassar, 2021)
This study aimed at discovering the degree of professional competence of elementary school’s mathematics teacher through Team Work Teachers (TWT) which trained and untrained by MEQIP, and also at examining to what extend the difference of professional competence level of elementary school;s mathematics teacher through TWT which trained and untrained by MEQIP at Barru. This study was descriptive and inferential research.The data were analyzed by using descriptive statistics analysis and inferential statistcs analysis. The result of the level of professional competence of elementary school’s mahtematics teachers by TWT not by MEQIP was in average category, and likewise, teachers’ competence in mastering advance program required serious attention because. The level of professional competence of elementary school’s mathematics TWT trained by MEQIP was in good category, and teachers’ competence in compiling program of elementary school was undoubted because need tobe improved by giving sufficient facilities.